PELATIHAN PERINEAL MASSAGE SEBAGAI UPAYA PENCEGAHAN RUPTUR PERINEUM SAAT PERSALINAN - Palifiana, Dheska Arthyka; Khadijah, Sitti; Widayati, Ririn Wahyu; Anggraini, Dita Septian (Stikes Yarsi Mataram, 2025)
Perineal tears affect approximately 85% of women during childbirth, with 60-70% requiring sutures. These tears are common in nearly all vaginal deliveries, highlighting the need for effective preventive strategies, such as perineal massage. This community service project aimed to enhance the health outcomes of pregnant and birthing women by reducing the incidence of perineal rupture during childbirth. The project involved educational sessions on perineal massage and hands-on training. Conducted in August and September 2023 at the Mantrijeron Health Center in Yogyakarta, the program included 25 participants. The results of the Community Service Program (PKM) showed that the characteristics of the respondents were mostly in the healthy reproductive age category (96%), primigravida parity (56%), third trimester (60%), and had never done perineal massage (96%). There was an increase in knowledge about perineal massage before and after the training of 20,800, with a p-value of 0.0002, which means that perineal massage training was effective in increasing the knowledge and skills of pregnant women. The conclusion of this PkM activity is that perineal massage training is effective in increasing the knowledge and skills of pregnant women.